2021
DOI: 10.3390/ijms22126409
|View full text |Cite
|
Sign up to set email alerts
|

In-Pero: Exploiting Deep Learning Embeddings of Protein Sequences to Predict the Localisation of Peroxisomal Proteins

Abstract: Peroxisomes are ubiquitous membrane-bound organelles, and aberrant localisation of peroxisomal proteins contributes to the pathogenesis of several disorders. Many computational methods focus on assigning protein sequences to subcellular compartments, but there are no specific tools tailored for the sub-localisation (matrix vs. membrane) of peroxisome proteins. We present here In-Pero, a new method for predicting protein sub-peroxisomal cellular localisation. In-Pero combines standard machine learning approache… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
36
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

4
5

Authors

Journals

citations
Cited by 25 publications
(39 citation statements)
references
References 54 publications
3
36
0
Order By: Relevance
“…The performance in terms of accuracy is 0.83. The in-depth analysis of the In-Mito predictor is available in the original paper [16]. Datasets are available at https://github.com/MarcoAnteghini/.…”
Section: Processing Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The performance in terms of accuracy is 0.83. The in-depth analysis of the In-Mito predictor is available in the original paper [16]. Datasets are available at https://github.com/MarcoAnteghini/.…”
Section: Processing Methodsmentioning
confidence: 99%
“…SeqVec showed similar results and optimal performance for predicting subcellular localisation [10]. However, their potential has been explored for highly specific tasks, such as sub-organelle localisation, just recently [16]. In particular, their usage can be adapted for sub-peroxisomal and sub-mitochondrial protein localisation.…”
Section: Introductionmentioning
confidence: 99%
“…The objective of this core is to calculate the embedding representations for protein sequences. For protein sequence encoding/embedding, recent studies have shown the superior performance of deep learning-based methods compared to traditional methods [23,24]. Accordingly, we only compared one-hot encoding to show the difference between these two kinds of embedding in this study.…”
Section: Proposed Frameworkmentioning
confidence: 99%
“…The PTS1 receptor PEX5 recognises a C-terminal tripeptide (SKL-type), whereas PEX7 recognises a nonapeptide within the N-terminus ( Walter and Erdmann, 2019 ; Kunze, 2020 ). Several predictors have been developed to identify peroxisomal proteins, their PTS, and their sub-peroxisomal location ( Kunze, 2018 ; Anteghini et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%